2020
DOI: 10.1016/j.heliyon.2020.e03444
|View full text |Cite
|
Sign up to set email alerts
|

FRnet-DTI: Deep convolutional neural network for drug-target interaction prediction

Abstract: The task of drug-target interaction prediction holds significant importance in pharmacology and therapeutic drug design. In this paper, we present FRnet-DTI, an auto encoder and a convolutional classifier for feature manipulation and drug target interaction prediction. Two convolutional neural neworks are proposed where one model is used for feature manipulation and the other one for classification. Using the first method FRnet-1, we generate 4096 features for each of the instances in each of the datasets and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…Docking simulation is the most successful method in drug-target interaction prediction when a three dimensional native structure of the target protein is available [ 10 ]. However, it is a time-consuming and expensive process to determine the native structure of a protein by sophisticated methods like X-ray Crystallography [ 11 ]. Thus, the 3D-structure of proteins are often unavailable.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Docking simulation is the most successful method in drug-target interaction prediction when a three dimensional native structure of the target protein is available [ 10 ]. However, it is a time-consuming and expensive process to determine the native structure of a protein by sophisticated methods like X-ray Crystallography [ 11 ]. Thus, the 3D-structure of proteins are often unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…These subdatasets have been used in a large number of related papers [ 14 , 15 , 16 , 17 , 18 , 19 ]. Due to the small number of known validated interactions among drug-target pairs, the unlabeled interaction pairs are considered as negative samples in most research and thus they outnumber positive samples [ 6 , 11 , 20 , 21 , 22 ]. The imbalance of DTI datasets is a major problem in supervised learning [ 11 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A convolutional neural network (CNN)-based method proposed by Öztürk et al [30], using only sequence information and performing DTIs prediction on Davis and KIBA dataset with the AUPR values of 0.714 and 0.788, respectively. Rayhan et al [31] proposed the FRnet-DTI, using autoenconder and CNN for feature extraction and classification. The AUC and AUPR values on the gold standard dataset showed that FRnet-DTI could significantly boost the DTIs prediction performance.…”
Section: Introductionmentioning
confidence: 99%